Effects of complete androgen blockade for 12 and 24 weeks on the pathological stage and resection margin status of prostate cancer. Issue 7 (1st July 2002) - Selli, C; Montironi, R; Bono, A; Pagano, F; Zattoni, F; Manganelli, A; Selvaggi, F P; Comeri, G; Fiaccavento, G; Guazzieri, S; Lembo, A; Cosciani-Cunico, S; et al.
Abstract : Aims: To compare the pathological stage and surgical margin status in patients undergoing either immediate radical prostatectomy or 12 and 24 weeks of neoadjuvant hormonal treatment (NHT) in a prospective, randomised study. Methods: Whole mount sections of 393 radical prostatectomy specimens were evaluated: 128 patients had immediate surgery, 143 were treated for 12 weeks and 122 for 24 weeks with complete androgen blockade. Results: Histopathology revealed organ confined tumours in 40.4% of patients with clinical stage B disease in the immediate surgery group, whereas 12 and 24 weeks of NHT increased the number of organ confined tumours to 54.6% and 64.8%, respectively. Among patients with clinical stage C tumours, pathological staging found organ confined disease in 10.4%, 31.4%, and 61.2% in the immediate surgery, 12 weeks of NHT, and 24 weeks of NHT groups, respectively. Preoperative NHT caused a significant decrease in positive margins both in patients with clinical stage B and C disease. The extent of margin involvement was not influenced by preoperative treatment. Conclusions: Neoadjuvant androgenic suppression is effective in reducing both the pathological stage and the positive margin rate in patients with stage B and C prostatic cancer undergoing radical surgery. Some beneficial effects are evident in those patients treated for 24 weeks, and it is reasonable to assume that the optimal duration of NHT is longer than three months.